Population structure of Phytophthora infestans collected on potato and tomato in Italy. (29th August 2021) - Saville, Amanda C.; La Spada, Federico; Faedda, Roberto; Migheli, Quirico; Scanu, Bruno; Ermacora, Paolo; Gilardi, Giovanna; Fedele, Giorgia; Rossi, Vitorrio; Lenzi, Nicolo; Testa, Antonino; Bechir Allagui, Mohamed; et al.
Abstract: Late blight caused by the oomycete Phytophthora infestans is a disease of potato and tomato of worldwide relevance and is widespread throughout Europe and the Mediterranean region. While pathogen populations in northern Europe have been sampled and characterized for many years, the genetic structure of populations from southern Europe, including Italy, has been less studied. Between 2018 and 2019, we collected 91 samples of P . infestans from potato and tomato crops in Italy, Algeria, and Tunisia on FTA cards and genotyped them using 12‐plex microsatellites. These samples were compared to genotypes of P . infestans previously collected within the framework of the EuroBlight network and from published sources. Four clonal lineages were identified: 13_A2 (Blue 13), 2_A1, 23_A1, and 36_A2. Two other isolates collected could not be matched to any currently known clonal lineage. The 13_A2 and 36_A2 lineages were found exclusively in southern Italy and Algeria, while 2_A1 was only found in Algeria. This is the first report of the 36_A2 lineage in Italy. Two isolates from Solanum nigrum were 13_A2, suggesting this weed host could be a reservoir of inoculum. The 23_A1 lineage was found widely on infected tomato crops in Italy and is the same as the lineage US‐23 that is widespread in North America. Differences in genotypes across the country suggests that there may be different sources of introduction into Italy, possibly via infected seed tubers from other countries in Europe, tubers for consumption from North Africa, or tomatoes. Abstract : The genetic structure of Phytophthora infestans was examined in Italy using microsatellite markers; 23_A1 was the dominant clonal lineage on both potato and tomato. This is also the first report of the 36_A2 clonal lineage in Italy.